062 Pembrolizumab induced lambert-eaton myasthenic syndrome. (23rd August 2021) - Ashhurst, Jasmine; Haddad, Rami; Zielinski, Rob
Abstract : Case Report: Lambert-Eaton Myasthenic Syndrome (LEMS) is a neuromuscular disorder caused by antibodies directed to the presynaptic voltage-gated calcium channel. It is often paraneoplastic, most commonly associated with Small Cell Lung Cancer (SCLC). This report outlines the case of a patient who developed LEMS secondary to pembrolizumab treatment for metastatic melanoma. An 82 year-old female presented to hospital 1 week after cycle 2 of pembrolizumab treatment for metastatic melanoma. On examination, she was found to have dysphagia, ocular muscle weakness and generalised weakness (most markedly weakness in hip flexors). Her weakness was fatigable and she had a waddling gait. Clinical picture was consistent with a clinical diagnosis of LEMS rather than myositis, which was confirmed by elevated anti-VGCC antibodies and response to Acetylcholinesterase inhibitors. Results: Anti-VGCC antibodies elevated at 119pM(<30). Transiently elevated CK, negative myositis autoantibodies, negative anti-MuSK antibodies, negative AChR antibodies. Although repetitive nerve stimulation did not show increment in the right ulnar CMAP after isometric muscle activation, the clinical picture was consistent with LEMS. Marked improvement to treatment with oral prednisone and pyridostigmine. Due to side effects, pyridostigmine was changed to 3, 4-Diaminopyridine therapy with excellent response. Steroids were weaned off and the patient is adequately controlled on 3, 4-Diaminopyridine. Conclusion: Our case report shows that LEMS can arise as a result of an immune-related adverse event (irAE) to pembrolizumab; an Anti-PD-1 Monoclonal Antibody. The immune response persists after cessation of this checkpoint inhibitor medication. It is important to recognise and treat this condition early.